2009
DOI: 10.1677/erc-08-0337
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of secretion of CXC α-chemokine CXCL10 in papillary thyroid cancer: modulation by peroxisome proliferator-activated receptor-γ agonists

Abstract: In papillary thyroid carcinomas (PTCs), oncogenes activate a transcriptional program including the upregulation of CXCL10 chemokine, which stimulates proliferation and invasion. Furthermore, peroxisome proliferator-activated receptor-g (PPARg) activators thiazolidinediones (TZDs) modulate CXCL10 secretion in normal thyroid follicular cells (TFC), and inhibit PTC growth. Until now, no study has evaluated the effect of cytokines on CXCL10 secretion in PTCs, nor the effect of PPARg activation. The combined effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 43 publications
2
60
0
Order By: Relevance
“…Antonelli and colleagues have reported that patients with autoimmune thyroiditis and Grave disease have elevated serum levels of CXCR3 ligands and that primary thyrocytes can be stimulated to secrete CXCL11 after treatment with IFNa, b, and g (31, 32). Moreover, it has been shown that PTC cells are more prone to secrete CXCL10 than normal thyroid follicular cells upon stimulation with IFNg (33). We show that ATC cells secrete significantly higher levels of CXCL10 than PTC cells after stimulation with minute doses of IFNg.…”
Section: Discussionmentioning
confidence: 55%
“…Antonelli and colleagues have reported that patients with autoimmune thyroiditis and Grave disease have elevated serum levels of CXCR3 ligands and that primary thyrocytes can be stimulated to secrete CXCL11 after treatment with IFNa, b, and g (31, 32). Moreover, it has been shown that PTC cells are more prone to secrete CXCL10 than normal thyroid follicular cells upon stimulation with IFNg (33). We show that ATC cells secrete significantly higher levels of CXCL10 than PTC cells after stimulation with minute doses of IFNg.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, besides type I and Type II interferons which were previously shown to inhibit the secretion of CXCL8 [13,15], other potentially interesting molecules to be tested for their CXCL8 inhibiting effects could include PPAR-c agonists. This appears to be supported by the evidences provided by Antonelli et al who reported that PPAR-c agonists display antineoplastic activity [25,26] and inhibit the secretion of several chemokines in primary cultures of thyroid cancer cells [27,28]. With specific regards to CXCL8, pioglitazone (a potent PPAR-c agonist) was demonstrated to inhibit the TNF-a induced CXCL8 secretion in endometriotic stromal cells [29] and to suppress CXCL8 mRNA expression in pancreatic cancer cell lines [30].…”
Section: Discussionmentioning
confidence: 66%
“…However, the relative potency of PPARa agonists on the inhibition of the secretion of CXC chemokine is higher than that of PPARg ligands. This could suggest that PPARa agonists may act, at least in part, through different pathways than PPARg agonists (Marx et al 2000, Schaefer et al 2005, Lombardi et al 2008, Antonelli et al 2009b.…”
Section: Discussionmentioning
confidence: 99%